Ocular manifestations of a hospitalised patient with confirmed 2019 novel coronavirus disease - Chen, Lu; Liu, Meizhou; Zhang, Zheng; Qiao, Kun; Huang, Ting; Chen, Miaohong; Xin, Na; Huang, Zuliang; Liu, Lei; Zhang, Guoming; Wang, Jiantao (British journal of ophthalmology, 2020)
PurposeTo report the ocular characteristics and the presence of viral RNA of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in conjunctival swab specimens in a patient with confirmed 2019 novel coronavirus disease (COVID-19).Participant and methodsA 30-year-old man with confirmed COVID-19 and bilateral acute conjunctivitis which occurred 13 days after illness onset. Based on detailed ophthalmic examination, reverse transcription PCR (RT-PCR) was performed to detect SARS-CoV-2 virus in conjunctival swabs. The ocular characteristics, presence of viral RNA and viral dynamics of SARS-CoV-2 in the conjunctival specimens were evaluated.ResultsSlit lamp examination showed bilateral acute follicular conjunctivitis. RT-PCR assay demonstrated the presence of viral RNA in conjunctival specimen 13 days after onset (cycle threshold value: 31). The conjunctival swab specimens remained positive for SARS-CoV-2 on 14 and 17 days after onset. On day 19, RT-PCR result was negative for SARS-CoV-2.ConclusionSARS-CoV-2 is capable of causing ocular complications such as viral conjunctivitis in the middle phase of illness. Precautionary measures are recommended when examining infected patients throughout the clinical course of the infection. However, conjunctival sampling might not be useful for early diagnosis because the virus may not appear initially in the conjunctiva.